Dr. Google Will See You Now: Google's Health Information Previews and Implications for Consumer Health. Issue 2 (2nd April 2020) - Scull, Amanda
Abstract: The aim of this exploratory study was to identify the sources of information provided in Google preview features, specifically the knowledge panels and featured snippets, when searching for health information online, with the goal of informing the development of consumer health programs and materials. In a search of the top ten health-related Google searches of 2018, the quality of information sources in the preview content varied both within and between sources. Librarians' knowledge of how a Google search responds to health inquiries of local interest can help them fill in gaps and curate or create more informative health materials for consumers.